Relationship between diagnostic accuracy and self-confidence among medical students when using Google search: A mixed-method study - Yasutaka Yanagita; Kosuke Ishizuka; Daiki Yokokawa; Kiyoshi Shikino (PLoS ONE, 2025)
Background With the growing volume of medical information, proficiency in utilizing clinical decision support systems (CDSSs) is increasingly important for physicians. Further, research has primarily focused on CDSSs’ accuracy for specific symptoms, diseases, and treatments, but the extent to which CDSSs contribute to the clinical reasoning process and evaluation of their output remains unclear. While Google is not a traditional CDSS, previous studies have evaluated its role as a diagnostic support tool, demonstrating its ability to assist physicians in retrieving relevant medical information and influencing diagnostic decision-making. Objective This study aimed to assess whether using Google search can enhance diagnostic accuracy and confidence among medical students, and to evaluate how the interpretation of search results influences their diagnostic confidence. Methods Forty-eight fifth-year medical students in clinical clerkship at Chiba University Hospital were presented with ten clinical scenarios in text format. Initially, they provided the most likely diagnosis without assistance and recorded their confidence levels. Subsequently, they used Google search to revisit their diagnoses and confidence levels, using a 7-point Likert Scale. Focus group interviews were conducted to discuss changes in confidence, and the interviews were analyzed qualitatively using content analysis. A mixed-methods analysis compared the average number of correct diagnoses and confidence levels before and after using Google search. Results In total, 470 responses from 48 fifth-year medical students were evaluated after excluding 10 inappropriate responses. Correct diagnoses increased from an average of 63.6% without assistance to 76.2% using Google search (P < .001), and confidence levels rose from 4.9 to 5.9 (P < .001). Qualitative analysis of higher-confidence responses identified 108 codes within 17 subcategories related to diagnostic processes. Conclusions This study underscores the value of using Google search in medical education to enhance diagnostic skills and confidence. The improvement in accuracy and confidence among students demonstrates the supportive role of Google search in clinical reasoning and education. This highlights the need for educators to teach discernment in information analysis to ensure optimal use of CDSS in medical training. Proper integration of these tools is crucial for developing future physicians capable of effectively navigating vast amounts of medical data.